The importance of low-density lipoprotein cholesterol measurement and control as performance measures: A joint clinical perspective from the National Lipid Association and the American Society for Preventive Cardiology - Salim S. Virani; Karen Aspry; Dave L. Dixon; Keith C. Ferdinand; Paul A. Heidenreich; Elizabeth J. Jackson; Terry A. Jacobson; Janice L. McAlister; David R. Neff; Martha Gulati; Christie M. Ballantyne (Elsevier, 2023)
Despite the established role of low-density lipoprotein cholesterol (LDL-C) as a major risk factor for cardiovascular disease (CVD), and the persistence of CVD as the leading cause of morbidity and mortality in the United States, national quality assurance metrics no longer include LDL-C measurement as a required performance metric. This clinical perspective reviews the history of LDL-C as a quality and performance metric and the events that led to its replacement. It also presents patient, healthcare provider, and health system rationales for re-establishing LDL-C measurement as a performance measure to improve cholesterol control in high-risk groups and to stem the rising tide of CVD morbidity and mortality, cardiovascular care disparities, and related healthcare costs.